Lack of Cystatin B Protein as a Cause Of Myoclonic Epilepsy - Amaral, O. (2012)
Publicado em: Molecular Genetics and Metabolism 105 (2012) S15–S69. Disponível em: http://www.sciencedirect.com/science/article/pii/S1096719211004343